The Effectivity Of 150 g/L Metamifop Herbicide To Identify And Control Weeds In Paddy Field Cultivation (Oryza Sativa L) - Dewi Hernawati; Diah Ika Putri; Dita Febriany; Arrin Rosmala (Department of Crop Science, Faculty of Agriculture, Andalas University, 2023)
Weeds are one of the obstacles to the growth of lowland rice cultivation which can reduce the quantity of rice yields so that weeds need to be controlled. This study aims to determine the effect of metamifop 150 g/L herbicide to control weeds in lowland rice cultivation. The experiment was carried out on paddy rice cultivation land in Langansari Village, Tarogong Kaler Cipanas District, Garut Regency, West Java, from November 2022 to February 2023. The experiment used a Randomized Block Design (RBD) with six treatments and four replications. The experiment consisted of four treatments with the active ingredient metamifop 150 g/L at a dose of A: 5.4 ml, B: 7.2 ml, C: 9.0 ml, D: 10.80 ml, E: manual weeding treatment and F : control treatment with no weed control. The results showed that the application of the herbicide with the active ingredient metamifop 150 g/L at a dose of D: 10.80 ml was able to suppress weed growth but the results were not significantly different from the dose of 5.4 ml which was the lowest dose to reduce weed resistance and plant residues so that dose A : 5.4 ml able to suppress the growth of weeds Echinochloa crusgalli, Monochoria vaginalis, Cyperus rotundus, Spenochlea zeylanica, Panicum repens, Cyperus difformis and total weeds.